Anaerobic Digestion Technology for Biogas Production: Current Situation in Nigeria (A Review) - Adebare Johnson Adeleke; O M Ajunwa; J A Golden; U E Antia; A T Adesulu-Dahunsi; O A Adewara; O D Popoola; E O Oni; B T Thomas; Y Luka (UMYU Journal of Microbiology Research)
In view of the nation's vast agricultural resources, crop residues, animal manure, municipal waste, and wastewater sludge may be transformed into renewable energy, potentially a source of revenue. Biogas production offers cleaner, sustainable solutions across the nation. The compass of supportive policy and regulation emerges, guiding investment toward transformative shores. Various "Waste-to-Energy" academic researches and pilot projects illuminate paths to energy generation, waste management and sustainability with the prospects of a viable bioeconomy. The application of anaerobic digestion technology contributes to a greener and more sustainable energy future. In Nigeria, biogas production holds multifaceted benefits which include energy sustainability waste management, and climate change mitigation. By harnessing organic waste, energy source diversification reduces reliance on fossil fuels. Biogas mitigates environmental pollution, converts waste to value, which is key to climate goals. Sustaining biogas production requires incentives, research, expertise, public awareness, and infrastructure. Collaboration and strategic partnerships will likely accelerate Nigeria's biogas production potential. In conclusion, this review underscores the immense potential of biogas production in Nigeria. It seeks to enliven the discussion for fostering efficient management of the abundant organic resources, supportive policies, public engagement, technological advancements, and partnerships that can bring about a wider implementation of biogas production projects across Nigeria towards a greener and sustainable energy future.